PaRIS Field Trial Report - van den Berg, Michael (OECD Publishing, 2024)
As populations age and the number of people with chronic conditions increases, countries need to assess how their health systems perform with regard to the management of chronic conditions. OECD's Patient-Reported Indicator Surveys (PaRIS) initiative aims to measure outcomes and experiences of healthcare as reported by patients with chronic conditions as part of the efforts to improve quality of care. The PaRIS survey, an international survey of people living with chronic conditions who are managed in primary care, is implemented in twenty countries. Following a rigorous design and development phase, the PaRIS survey was field-tested in participating countries. This paper reports on the implementation and the results of the Field Trial. The Field Trial provided important lessons which have been used to improve the survey tools and the implementation of the Main Survey
Keywords: Social Issues/Migration/Health